2021
DOI: 10.1111/liv.15030
|View full text |Cite
|
Sign up to set email alerts
|

Association between circulating bile acid alterations and nonalcoholic steatohepatitis independent of obesity and diabetes mellitus

Abstract: Background and Aims Bile acid (BA) dysregulation is related to not only metabolic diseases but also nonalcoholic fatty liver disease (NAFLD). We investigated whether circulating BA levels are altered according to the histological severity of NAFLD independent of metabolic derangements. Methods Global metabolic profiling and targeted BA analysis using sera collected from biopsy‐proven no‐NAFLD (n = 67), nonalcoholic fatty liver (NAFL) (n = 99), and nonalcoholic steatohepatitis (NASH, n = 75) subjects were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Consistently, clinical studies have demonstrated that primary and secondary CBAs are tightly associated with NAFLD progression and NASH severity [30,48,49,51,52] . A recent study reported that elevated hepatic taurochenodeoxycholic acid (TCDCA) and taurocholic acid (TCA) in NAFLD patients was associated with symptom onset, disease progression, or death [51] .…”
Section: Bile Acids and Sphingolipids In Nafldmentioning
confidence: 84%
See 2 more Smart Citations
“…Consistently, clinical studies have demonstrated that primary and secondary CBAs are tightly associated with NAFLD progression and NASH severity [30,48,49,51,52] . A recent study reported that elevated hepatic taurochenodeoxycholic acid (TCDCA) and taurocholic acid (TCA) in NAFLD patients was associated with symptom onset, disease progression, or death [51] .…”
Section: Bile Acids and Sphingolipids In Nafldmentioning
confidence: 84%
“…[5,40] In the recent decade, extensive studies from animal models and human patients have found that NAFLD disease progression is closely associated with bile acid dysregulation and sphingolipid homeostasis. [48][49][50][51][52][53][54][55][56][57][58][59][60] Mechanisms linking bile acid metabolism to the development of NAFLD Consistently, clinical studies have demonstrated that primary and secondary CBAs are tightly associated with NAFLD progression and NASH severity. [30,48,49,51,52] A recent study reported that elevated hepatic taurochenodeoxycholic acid (TCDCA) and taurocholic acid (TCA) in NAFLD patients was associated with symptom onset, disease progression, or death.…”
Section: Bile Acids and Sphingolipids In Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence suggests that BA metabolism is associated with liver disease and may be a potential target for its treatment ( Jung et al, 2021 ). Many natural products have been shown to alleviate or prevent NAFLD by regulating BA metabolism ( Huang et al, 2019 ; Xiong et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, bile acids themselves are capable of influencing metabolic processes, and possibly behavior, through the farnesoid X receptor and Takeda G protein-coupled receptor 5, which are also found in the brain, and by inducing release of glucagon-like peptide 1 and fibroblast growth factor 19 (Huang et al, 2016;Keitel et al, 2010;Maruyama et al, 2002;Mertens et al, 2017). Given that increased bile acid levels have been associated with fatty liver disease, while reduced bile acid levels seem to have a protective effect against fatty liver disease (Bajaj, 2019;Clifford et al, 2021;Jung et al, 2021), future work is needed to shed light on the role of ghrelin-related changes in bile acids, if any, in different alcohol-related outcomes including alcoholassociated liver disease.…”
Section: Discussionmentioning
confidence: 99%